TRANSFORMASI DIGITAL DALAM MANAJEMEN PENDIDIKAN ISLAM: TELAAH KRITIS TERHADAP INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN BERBASIS NILAI-NILAI ISLAMI - Hasim Halim (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2025)
Digital transformation has significantly impacted the management of Islamic education, particularly in integrating technology into value-based Islamic learning. This study aims to analyze the implementation of digital technology in Islamic education and its effects on learning effectiveness and the reinforcement of Islamic values. Using a qualitative approach with a library research method, this study examines various literature sources, including books, scientific journals, and official documents. Data collection is conducted through documentation techniques, followed by content analysis to identify key patterns and concepts from the reviewed literature. The findings reveal that digitalization in Islamic education offers vast opportunities for enhancing accessibility and learning effectiveness but also presents challenges in maintaining Islamic values within digital environments. To address these challenges, strategies that integrate Islamic principles into technology use and strengthen the role of educators and institutions in guiding students are essential. Data validity is ensured through source triangulation and conceptual validity based on relevant theoretical frameworks. Thus, this study provides a theoretical contribution to developing a digital-based Islamic education management model that remains firmly grounded in Islamic values.